O encontro entre Douglass North e Celso Furtado em 1961: Vis\~oes alternativas sobre a economia nordestina - Mauro Boianovsky; Leonardo Monteiro Monasterio (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– In June 1961 the American economist Douglass North visited Brazil for 3 weeks, for a mission organized by the US State Department and Instituto Brasileiro de Economia (IBRE-FGV). The goals of North's Brazilian mission were to evaluate Sudene's plans for the Northeast - which involved meeting Celso Furtado -, to give lectures on regional growth and assess the quality of economics courses in the country. This paper deals with the "meeting" between North and Furtado in the broad sense of the word, that is, not only the actual meeting of June 20 1961, but also the meeting of their respective ideas about how to develop the economy of the Northeast. It is based on new material formed by original documents of the "Douglass North Papers" collection held at Duke University Library.
Keywords: B25; N01; 330; Douglass North; Celso Furtado; Northeast; migration; development